RES-360 Degrees - Resilience in Education Systems : Rapid Assessment Manual - World Bank (Washington, DC, 2014)
This manual presents the objectives and procedures for application of the Education Resilience Approaches (ERA) Program s first major tool to aid in assessing resilience in education systems. The RES-360 rapid assessment approach helps both national education institutions (e.g. Ministries of Education) and schools to identify the risks confronting education communities, especially students. It also points to the assets and positive engagement in schools and communities that, if recognized and supported, can make national education programs more relevant and effective in contexts of adversity. In addition to the RES-360 evaluation, ERA is developing tools to assess classroom and school opportunities to foster resilience (RES-School) and a mixed-methods research approach for local researchers and higher education institutions to guide their contributions to education resilience evidence in their countries (RES-Research). As the application of these diagnostic and research tools expands, ERA hopes to systematically collect and disseminate the growing global evidence regarding the resilience of education systems in contexts of adversity and their contributions to mitigating the sources of such adversity.